Hyperplasia of Wistar rat tongue mucosa due to exposure to cigarette side-stream smoke - Nurina Febriyanti Ayuningtyas; Grahania Octaviono Mahardika; Bagus Soebadi; Adiastuti Endah Permadiati; Saka Winias; Hening Tuti Hendarti; Rosnah Binti Zain (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Hyperplasia, a condition whereby an excessive number of cells are produced due to their uncontrolled division, represents a common symptom of carcinogenesis. Cancer is a physical manifestation of cell malignancy resulting from abnormal proliferation. Globally, oral cancer currently constitutes the sixth largest lethal form of the condition. The most common etiology of oral cancer is tobacco of which cigarettes are the most popular related product. The health risks associated with cigarette smoke not only affect active smokers but also individuals who ingest it passively. Sidestream smoke comes from the lighted end of  a burning tobacco product such as a cigarette, pipe or cigar and contains nicotine and many harmful cancer-causing chemicals. Inhaling sidestream smoke increases the risk of lung and other types of cancer. Purpose: The purpose of this study was to understand how sidestream cigarette smoke initiates precancerous changes, in this case hyperplasia, in the oral mucosa epithelium of Wistar rats. Methods: The subjects were divided into three groups, a 4-week treatment group (P1), an 8-week treatment group (P2), and a control group (K), each consisting of ten subjects. The subjects were exposed to a daily two-cigarette dose of smoke. The experiment used a post-test only control group design. All samples were sacrificed during the fourth and eighth weeks. Haematoxylin-eosin staining was performed on the tongues of the Wistar rats to establish the presence of hyperplasia. Data was analyzed using a one-way ANOVA test. Results: After the Wistar rats had been exposed to cigarette smoke, an increased degree of epithelial cell proliferation (hyperplasia) showed a significant difference with a p-value <0.05 during the eighth week. Conclusion: Exposure to cigarette sidestream smoke induces increased epithelial cell proliferation (hyperplasia) in Wistar rats.